Psychological and pedagogical principles of the problem of technologies of game simulation (Actual Problems of Psychology in Educational Institutions, 2019)
n the article, are presented m ain scientific approaches t o theproblems of game modeling, the characteristics of the game are presented, onthe basis of the implementation of the game modeling. The role of the gamemodel in the preparation of students until May of professional and pedagogicalactivity was assigned. The necessity of introduction of interactive technologiesinto the educational process is substantiated, attention is focused on thetechnologies of gaming modeling while organizing the educational process inthe institution of higher education.
Keywords: game, educational game, simulation, game simulation technology, didactic game, role-playing game, business game